Political Advertising In Nigeria And Adherence To Codes: Political Marketing Communications Within The Rubrics Of Laws - Ifeanyi Martins NWOKEOCHA (Cita konsultindo, 2024)
This study investigates the intersection of political advertising and adherence to regulatory codes within Nigerian elections, with a specific focus on the 2023 presidential election. Political advertising plays a crucial role in electoral campaigns, leveraging various platforms, including social media, to reach and influence voters. However, concerns arise regarding the compliance of these advertisements with the ethical guidelines set by the Nigeria Broadcasting Cod (NBC), Advertising Regulatory Council of Nigeria (ARCON) and the Independent National Electoral Commission (INEC). This research aims to evaluate the extent to which political advertisements adhered to these codes and to assess the impact of the legal frameworks on political marketing strategies. This paper examines political marketing by utilizing research from various journals and papers, focusing on how politicians adhere to the rules and regulations provided by regulatory bodies. Preliminary findings suggest that while some political advertisements complied with NBC, ARCON and INEC regulations, numerous instances of non-compliance were evident, particularly in the use of misinformation and exploitative rhetoric. The study also highlights the challenges faced by regulatory bodies in enforcing these codes effectively. Moreover, the research explores how legal constraints influence the strategies of political marketers, revealing a tension between adherence to ethical guidelines and the competitive pressures of election campaigns. The findings underscore the need for stronger enforcement mechanisms, greater transparency, and enhanced public awareness to ensure ethical political advertising practices. This study contributes to the broader discourse on political communication and democratic integrity, offering insights and recommendations for improving regulatory frameworks and fostering more ethical political marketing in Nigeria.